Ekonomi Global dan Krisis Demokrasi - Winarno, Budi (Universitas Muhammadiyah Yogyakarta, 2012)
Since the fall of the Soviet Union led to the end of the Cold War, democracy and capitalism have become an unchallenged ideology. In the era of globalization, global economy and free market have not directly brought about democracy, and therefore it denies the argument of globalists. As a matter of fact, globalization has increasingly marginalized the roles of state, and even it has replaced them by the non-territorial actors or the super-states, namely international institutions, multinational corporations, and private organizations. Their roles of these territorial actors not only have become so strong and dominant in economy and politics, and therefore they have the power to control the world market, but also have threatened democracy. As a result, the roles of the states are coopted to serve the interest of corporations, and are detrimental for the interest of the citizens. Therefore, conventional democracy has to be redefined because it has not been adequate any more.